The prevalence of pruritus gravidarum and its relation with intrahepatic cholestasis of pregnancy - Choudhary, Leena; Kaur, Amrit Pal; Kaur, Tejinder; Kaur, Kiranjeet (International Journal of Research in Medical Sciences, 2023)
Background: Pruritus is a common complaint amongst pregnant woman, affecting 20% of them. This can be physiological or due to some specific dermatological conditions. Among them Intrahepatic cholestasis of pregnancy is most common cause and is characterized by pruritus with derranged liver enzymes and raised serum bile acid levels in the absence of any other liver pathology. It is associated with increased fetomaternal morbidity. Methods: This was a prospective study, conducted at Bebe Nanki Mother and Child Care Centre, Government Medical College, Amritsar in the Department of Obstetrics and Gynaecology with collaboration of Dermatology Department, from March 2021 to Aug 2022. After taking ethical approval, informed consent, detailed history, clinical and biochemical assessment was done and fetomaternal outcome was recorded. Results: Prevalance of pruritus was 20.8% amongst pregnant women, of which 24% patients were diagnosed having intrahepatic cholestasis of pregnancy (ICP) and 76% were labelled as NON ICP patients. Among NON ICP patients prevalence of pruritic urticarial papules and plaques of pregnancy was 32.10%. Majority intrahepatic cholestasis of pregnancy patients had moderately affected quality of life. Majority of pruritic patients had normal bilirubin levels and all intrahepatic cholestasis of pregnancy patients had raised serum Alanine transaminase, Aspartate transaminase, bile acids values. Meconium stained liquor, preterm delivery, Low birth weight, cesarean rates, NICU admissions rates were higher in intrahepatic cholestasis of pregnancy patients. Conclusions: Pruritus in pregnancy is a common condition. Dermatological opinion along with liver function tests should be done to know about the cause and severity of pruritus. Intrahepatic cholestasis of pregnancy (ICP) affects perinatal outcomes. So patients should be closely monitored to improve the fetomaternal outcome.